Pengaruh Implementasi Kebijakan Penerimaan Peserta Didik Baru Berdasarkan Sistem Zonasi Terhadap Kualitas Pelayanan Pendidikan Di Sman 1 Luwu Timur Kabupaten Luwu Timur - Lestari, Ayu Asmi; Madani, Muhlis; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to find out the effect of the implementation of the new student admission policy based on the zoning system on the quality of education services at Senior High School 1 East Luwu , East Luwu Regency. The method in this study used a mix method research method with survey research type. The sample were 88 people and the sampling method used random sampling and purposive sampling. The data were analyzed by using simple linear regression analysis. The results of this study showed that the analysis of the policy implementation variable falls into the